REVIEW OF ROBERT SPAEMANN'S PERSONS - Madigan, Arthur (Journal of religious ethics, 2010)
This review presents the principal themes of Robert Spaemann's Persons: The Difference between ‘Someone’ and ‘Something.’ To be a person is not to be identical with one's teleological nature, but rather, to have that nature. Personal consciousness is necessarily temporal consciousness. Persons have a range of distinctively personal acts, such as recognizing and respecting one another, understanding their lives as wholes, making judgments of conscience, promising, and forgiving. All members of the human species, whatever their stage of development or limitations, are persons. The present review also briefly considers certain objections that have been raised against Spaemann's position.